1995
DOI: 10.1021/bi00011a039
|View full text |Cite
|
Sign up to set email alerts
|

Doubly-lipid-modified protein sequence motifs exhibit long-lived anchorage to lipid bilayer membranes

Abstract: To understand better the potential functional importance of the dual-lipid modifications found in a number of intracellular proteins of eukaryotes, we have examined how "tenaciously" various doubly-lipid-modified peptides, with sequences and lipid modifications reflecting those found in intracellular proteins, are anchored to lipid bilayer membranes. Fluorescent-labeled peptides bearing dual-lipid modifications were incorporated into large unilamellar egg phosphatidylcholine/phosphatidylglycerol vesicles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
243
1
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(272 citation statements)
references
References 90 publications
24
243
1
4
Order By: Relevance
“…11, March 20001993; Silvius and l'Heureux, 1994;Shahinian and Silvius, 1995). A C15 farnesyl isoprenoid or an N-myristoyl group does not provide sufficient hydrophobicity to anchor a peptide stably to membranes.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…11, March 20001993; Silvius and l'Heureux, 1994;Shahinian and Silvius, 1995). A C15 farnesyl isoprenoid or an N-myristoyl group does not provide sufficient hydrophobicity to anchor a peptide stably to membranes.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 99%
“…However, the addition of a second lipid modification dramatically slows the rate of interbilayer transfer such that the peptide is essentially permanently anchored. Shahinian and Silvius (1995) suggested the kinetic bilayer-trapping model as a mechanism for targeting proteins to a specific membrane. The model proposes that a farnesylated or N-myristoylated protein diffuses through the cytosol transiently associating with all membranes until it encounters the site where the second lipid is added.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 99%
“…In a series of biophysical investigations of the thermodynamics of insertion of lipid-modified model peptides in vesicles, functioning as model membranes, the contribution of the lipids to lipopeptide membrane affinity was determined. [45][46][47] This showed that an Nmyristoyl or an S-farnesyl group alone cannot contribute enough hydrophobic character to maintain stable membrane insertion of peptides, and therefore also of proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Biophysical model experiments on the kinetics of transfer of lipidmodified peptides from one model membrane to another [49,50] showed that peptides and proteins that only carry a single lipid modification are rapidly inserted into the membrane (within seconds) yet they are also rapidly exchanged between two different membranes. The half time for transfer of a singly farnesylated or palmitoylated peptide is in the region of seconds.…”
Section: Methodsmentioning
confidence: 99%
“…In the kinetic trapping model (Peitzsch and McLaughlin, 1993;Shahinian and Silvius, 1995), palmitoylation acts in concert with two other types of acylation to ensure a stable interaction within membrane leaflets (Fig. 1B).…”
Section: Acylation Impacts On the Fate Of Proteinsmentioning
confidence: 99%